CATEGORICAL APPARATUS FOR REGIONAL INVESTMENT DEVELOPMENT RESEARCH - Buchynsky , O. (Theory and Practice of Public Administration, 2020)
Investment attractiveness of regions in the conditions of decentralization in Ukraine is one of the key directions of the state policy providing development of infrastructure of regions, increase of level of their production potential, growth of a level of vital activity of territorial communities and inhabitants of cities. The study of theoretical aspects of investment development of regions in the domestic science of “Public Administration” is impossible to study without studying the conceptual apparatus, its features, historical and structural and logical content. The author of the article considers the conceptual apparatus of the study of investment development of the regions in terms of public administration principles. Identified features of the concept of “investment”, helping to justify this term from related in economic and legal sciences. The study of the views of domestic and foreign scientists, the interpretation of this concept in scientific reference articles and manuals contributed to the formation of the author’s definition. As a result, investments are considered as objects that have a certain value as material value, natural resource, which can be included in the objects of entrepreneurial and other activities to obtain an effective useful result. In the article, the author gives numerous examples of the use of the concept of “investment” in research in the field of investment and investment activities, noting that scientists have not been able to find agreement on its interpretation in economics and law. It is proved that there is no single definition of this concept in regulations, which complicates the study of this topic in the field of science “Public Administration”. Thus, this issue has not been studied at the governmental level, especially in the context of the signed Association Agreement between Ukraine and the European Union. Analysis of recent research and publications. The issue of the essence of investment development of regions was studied by the classics of economic theory A. Smidt, J. Keynes, K. Marx. R. Averchuk, V. Bodrov, N. Baldych, A. Gavrilyuk, A. Gaiduk, A. Duk, V. Shevchuk, M. Shestak made a significant contribution among domestic scientists in the field of public administration. In the study of the categorical apparatus of investment development of regions, the scientific works of S. Dyachenko, A. Kozak, M. Krupka, T. Mayorova, A. Muzychenko, V. Novitsky, A. Peresadi, A. Filipenko, A. Yurkevich deserve attention. The purpose of the article is to conduct a study of the categorical apparatus of investment development of regions on the basis of the analysis of domestic and foreign scientific research of scientists, interpretations from various reference dictionaries and regulatory legal acts and to form their own vision of the definition of “investment” as a state-administrative category. Drawings and suggestions for those who have been presented to them. In this rite, ponyattya “іnvestitsії” їh characteristic that viznachennya sutnіsnih Find our spriyaє Process pobudovi State іnvestitsіynoї polіtiki on regіonalnomu rіvnі, realіzatsії vnutrіshnіh that zovnіshnіh great-power upravlіnskih aspektіv scho vіdіgraє vazhlivu role in pobudovі іnvestitsіynoї polіtiki regіonu, peredbachaє Complex analіz that upravlіnnya structural star ‘yazkami i vіdnosinami in regіonі, vklyuchayuchi vіdtvorennya lyudskogo kapіtalu, penny, fіnansovih, natural that іnformatsіynih resursіv, poslug Galuzo regіonalnoї virobnichoї i sotsіalnoї іnfrastrukturi, SSMSC zabezpechuyutsya for Relief regіonalnih rinkіv, formuyut sogodnі digit Chastain publіchnogo upravlіnnya that admіnіstruvannya them. In the future, in the future, the process of regional innovation within the framework of the state investment policy, both internal and external, so called. Vіdtvoryuvalny pіdhіd [18] Mauger become a promising rozvіdkoyu schodo zastosuvannya integrated mehanіzmu publіchnogo upravlіnnya structural zv’yazkami i vіdnosinami in regіonі, vklyuchayuchi vіdtvorennya lyudskogo kapіtalu, Penny, fіnansovih, natural that іnformatsіynih resursіv, poslug Galouzeau regіonalnoї virobnichoї i sotsіalnoї іnfrastrukturi, SSMSC zabezpechuyutsya for dopomoga regional markets, form a large part of the state’s links among the sub’ects of regional production.